Incentives as mediating variables in the relationship between antecedent factors and employee productivity: A systematic literature review - Ibrahim, Irmohizam; Abiddin, Norhasni Zainal (International Journal of Innovative Research and Scientific Studies, 2025)
In today's fast-changing business landscape, organizations are continually seeking ways to improve their employees' productivity. An important component of achieving such a goal is understanding the impact of performance on employees' productivity. This measure, also called labor productivity, is a key indicator of employees' efficiency and displays the quantity of output generated over a given time span. High productivity serves to develop a culture of excellence within organizations, leading to improved workplace environments. Productivity is directly linked to organizational success and profitability, as it ensures effective utilization of resources, higher output, and competitiveness within the marketplace. Understanding the many factors influencing employees' productivity within the organization is critical. It has previously been noted that employees' habits, quality of output, and time management play a vital role in productivity measurement. It’s important, however, to understand that organizational productivity among employees cannot be solely attributed to personal effort and abilities. External factors such as motivation, working environment, and their level of satisfaction have a major impact on employees' productivity. Rewards, especially, have been cited as intervening variables in the relationship between antecedent variables and employees' productivity.